PENGARUH BRAND IMAGE, CO – BRANDING, DAN CELEBRITY ENDORSEMENT TERHADAP KEPUTUSAN PEMBELIAN: (Studi pada Konsumen Haus! Graha Raya di Tangerang Selatan) - Dina Nur Hidayah; Ravindra Safitra Hidayat (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
There are so many food and beverage (fnb) businesses competing in Indonesia, one of which is Haus! that is still surviving today. The aim of this study is to assess the impact of Brand Image, Co-Branding, and Celebrity Endorsement on purchasing decisions. The population under investigation consists of consumers of Haus! Graha Raya in South Tangerang. This study utilizes a survey method involving 96 respondents selected using non-probability sampling techniques, specifically purposive sampling. Data analysis was conducted using SPSS version 26. All variables tested have met validity and reliability standards and have passed classical assumption tests, making the study deemed appropriate. The research findings reveal that Brand Image, Co-Branding, and Celebrity Endorsement have a significant impact on the purchasing decisions of Haus! Graha Raya consumers in South Tangerang.